Effect of Climate Change on Groundwater Age of Thailands Lower Chao Phraya Basin - Pinit Tanachaichoksirikun; Uma Seeboonruang (My University, 2019)
Abstract Water is indispensable for life, including, groundwater that the largest fresh water source. Groundwater sustainability is threatened by many factors, one is climate change which lead to flood and drought. Groundwater age is an indicator that can be applied for vulnerability assessment and sustainable groundwater management. This research focus on the changing of groundwater age under the effect of climate change using the steady-state three-dimensional mathematical simulation including, MODFLOW-2000 and MODPATH. In addition, the climate scenario including, IPSL-CM5A-MR that consist the increasing of carbon dioxide (Representative Concentration Pathways; RCP) between 2.6, 4.5 and 8.5 in the period 2017-2036. The results revealed groundwater age was highly distributed between 140 to 177,505 years with the average 18,665 years due to the distribution of groundwater recharge and pumping in the basin. In addition, the average groundwater age with RCP 2.6, 4.5 and 8.5 were decreased to 17,217, 15,960, 16,286 years from base case (18,665 years), respectively. Because the quantity of rainfall which contribute the hydraulic head, hydraulic gradient and velocity was changed. In conclusion, the groundwater sustainability in the Lower Chao Phraya basin was consistent during this period because the groundwater age was decreased by rainfall. However, the old groundwater, non-renewable groundwater could be conservative due to the distribution of groundwater age was increased.
Keywords: MODFLOW; Geophysics and Gravity Measurements